John Key the biofinancial entrepreneur. (2nd July 2016) - Jones, Campbell
ABSTRACT: Alongside the better known repudiations of truth that have risen to prominence since the 1970s—known variously in terms of postmodernism, identity politics, democratic materialism or simply university discourse—this article seeks to estimate the significance of the reactions against truth that are characteristic of finance. Finance is a collective subject or social movement in its own right, composed of a set of actors, devices, technologies and platforms which together constitute an apparatus that reacts against truths whenever and wherever they arise. This operates most clearly in the logic of risk management, a generalised technology that accompanies the financialisation of economy, politics and culture. The process of financialisation or rather what will be called here the 'biofinancialisation' that seeks to code life in the terms of finance, bears austere lessons about truth and resistance and these, in conjunction with new resistances from below, provide new prospects for radical politics and progressive social change today. These lessons we will learn from, among others, the 38th Prime Minister of New Zealand.